Vertical jump peak power estimation in young male gymnasts - Kochanowicz, A.; Niespodzinski, B.; Mieszkowski, J.; Kochanowicz, K.; Zasada, M. (Baltic Journal of Health and Physical Activity, 2016)
Background: There is a lack of peak power (PP) estimation for young gymnasts; therefore, the purpose was to derive a new regression equation predicting young gymnasts` PP and to validate and compare it with the previously published ones. Material/Methods: In the study, eighty young male gymnasts (age = 10.9 ±1.98 years; body mass = 33.5 ±7.45 kg) performed a countermovement jump on a force platform. Then, ¼ of the subjects were randomly assigned to a validation group and the rest served to develop a new linear regression equation using their body mass and vertical jump height (VJH). Results: In comparison, PP estimated by the new equation (1439.8 ±479.3 W) showed no significant (p > 0.05) differences with the actual PP (1400.8 ±542.8 W), whereas other previously published ones were different (p < 0.05). The developed new equation looked as follows: PP [W] = 73.81 x VJH [cm] + 34.66 x body mass [kg] -1617 (r2 = 0.75). Conclusions: According to a small systematic bias (38.97 W), the new equation can be used to predict PP of young gymnastic groups. The newly developed equation fits better the actual performance of gymnasts than the previous published ones.